Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1099/0022-1317-65-11-2067
|View full text |Cite
|
Sign up to set email alerts
|

Homology between Phages SPP1, 41c, 22a,  15 and SF6 of Bacillus subtilis

Abstract: SUMMARYBacteriophages SPP 1, 4 lc, 22a, p 15 and SF6 of Bacillus subtilis share a common and specific host receptor site for adsorption. Experiments described here have established the relatedness between these phages. They were indistinguishable on the basis of hostrange, plating efficiency, various growth parameters and serological properties. In addition, they shared the ability to carry out generalized transduction. They could be differentiated, however, by the restriction patterns of their DNAs, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…SPP1 phages were produced in B. subtilis YB886 (51) grown in LB medium and supplemented with 10 mM CaCl 2 just before infection (38). Isolated phage plaques (10 5 to 10 6 PFU) were used to generate confluent plate lysates (10 8 to 5 ϫ 10 8 PFU), and then the phages were amplified sequentially in small-and large-scale culture infections.…”
Section: Methodsmentioning
confidence: 99%
“…SPP1 phages were produced in B. subtilis YB886 (51) grown in LB medium and supplemented with 10 mM CaCl 2 just before infection (38). Isolated phage plaques (10 5 to 10 6 PFU) were used to generate confluent plate lysates (10 8 to 5 ϫ 10 8 PFU), and then the phages were amplified sequentially in small-and large-scale culture infections.…”
Section: Methodsmentioning
confidence: 99%
“…pha-2 mutants retained the capacity to adsorb phages at a wild-type rate, but phage-host complexes could be readily separated by dilution, showing the process to be wholly reversible. The mutation was found to be specific for SPP1 and related phages and was mapped, by PBS1-mediated transduction, in the vicinity of the ald-1 marker (29,30).…”
mentioning
confidence: 99%
“…pha-2 mutants retained the capacity to adsorb phages at a wild-type rate, but phage-host complexes could be readily separated by dilution, showing the process to be wholly reversible. The mutation was found to be specific for SPP1 and related phages and was mapped, by PBS1-mediated transduction, in the vicinity of the ald-1 marker (29,30).Based on the map position of the pha-2 locus and the availability of the complete sequence of the B. subtilis genome, we have now attempted to identify the gene required for SPP1 irreversible adsorption. The experiments described here identify yueB, an orthologue of pip, as the key gene involved in irreversible adsorption of SPP1.…”
mentioning
confidence: 99%
“…Quantitative analysis showed that an average of approximately 130000 copies of portal monomers are present per infected cell (30 min). This value represents a large excess relatively to the theoretical amount of gp6 required to accomplish its structural role in the virion if we take into consideration the SPP1 burst size (260-560 infectious particles/cell depending on the experimental conditions [30]) and assume that the portal protein is also a 13-met in the phage particle [1]. The meaning of such high production of gp6 in infected cells is not yet understood.…”
Section: The Spp1 Portal Protein Cistronmentioning
confidence: 99%